Safety profile between fluoxetine and sertraline as antidepressants for pregnant women with depression disorder - Dewa Ayu Sri Handani; Mustikawati, Maria Sri Ayu; Parwatininghati, Ni Putu; Zulkarnaen; Akuba, Jusnita (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
Depression disorders are common in women of productive age, especially during pregnancy and peripartum period. Making a decision on the choosing of antidepressants is associated to the biggest concern about the risk of birth defects and major anomalies of their exposure. Decisions of antidepressant use not only involve considering the risks of medications exposure, but also the risks of untreated depression during pregnancy. Evaluation of the safety profile of selective reuptake inhibitors (SSRIs) which are commonly prescribed during pregnancy therefore urgently needed. This review aimed to compare two widely used SSRIs i.e. fluoxentine and sertraline as antidepressants for pregnant women with depression disorder. It is found that sertraline has more positive effects and more safe. Sertraline is well tolerated in pregnant women and breastfeeding mothers with depression disorder.